Istota ciągłości organizacyjnej w rozwijaniu zdolności uczenia się współczesnych przedsiębiorstw - Zgrzywa-Ziemak, Anna (Significance of organizational continuity for developing enterprises' learning capability, 2006)
In the paper the significance of integration organizational continuity and change for developing enterprises' learning capability was indicated. Especially the concept of organizational continuity was discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 413-420